When FOMO Overrides Trust: The Impact of Customer Reviews on Gen Z Buying Decisions - A. Rahmat Wahyu Aji; Mohamad Rifqy Roosdhani (Dinasti Review, 2026)
In this era of increasingly massive digital marketing, online customer reviews serve as a significant determinant of consumers’ purchasing decisions, notably among Gen-Z consumers, who are highly active across social networking platforms. This study aims to identify and examine how reviews affect purchasing decisions by incorporating Fear of Missing Out (FOMO) and trust as mediating factors in the Kopi Tiro setting. This research adopted a quantitative research design primary data were collected from 151 respondents through an online questionnaire. This study examines the role of customer reviews in influencing customer decisions and whether FOMO and trust can act as mediators. The findings of this study indicate that purchasing decisions among Gen-Z are more influenced by psychological factors such as FOMO than rational considerations based on trust. This study provides theoretical and practical implications for digital marketing strategies targeting Gen-Z consumers. Theoretically, this research is expected to enrich the literature in the field of marketing and consumer behavior. Practically, the results of this research can be utilized as a reference by entrepreneurs, especially in the culinary industry, in developing more effective digital marketing strategies by enhancing customer review management and capitalizing on the FOMO effect.